Second-Trimester Pregnancy Loss at an Urban Hospital - Debra S. Heller; Charlene Moorehouse-Moore; Joan Skurnick; Rebecca N. Baergen (Hindawi Limited, 2003)
Objectives: Second-trimester spontaneous pregnancy losses are less common than first-trimester losses, and are often associated with ascending infection and/or acute chorioamnionitis. A Medline search revealed only two large studies published in the recent literature, reporting incidences of chorioamnionitis of 39.3% and 58.2%, respectively. These studies did not address the use of histopathology for the identification of organisms. Since ascending infection is likely to be a significant cause of second-trimester loss in the inner-city population at the University Hospital in Newark, New Jersey, we sought to evaluate the usefulness of stains for microorganisms, which are rarely utilized on these specimens.